THE MODEL OF PARAMETRIC RESOURCES RATIONING IN THE ASSESSMENT OF RESOURCE PROVISION OF LARGE-SCALE DEVELOPMENT PROGRAMS - O. M. Pisareva (Модернизация, инновация, развитие, 2015)
The model of parametric resources rationing in the construction industry to address the problem of improving the justification methods of resource provision of strategic development programs with the budget financing is presented. The structure of parametric techniques rationing for the calculations consumption norms of labor, materials and machines (mechanisms) is proposed.